Using Precision Public Health to Manage Climate Change: Opportunities, Challenges, and Health Justice. Issue 4 (2020) - Ganesh, Chandra; Schmeltz, Michael; Smith, Jason; Johnson, Walter G.
Abstract : Amid public health concerns over climate change, "precision public health" (PPH) is emerging in next generation approaches to practice. These novel methods promise to augment public health operations by using ever larger and more robust health datasets combined with new tools for collecting and analyzing data. Precision strategies to protecting the public health could more effectively or efficiently address the systemic threats of climate change, but may also propagate or exacerbate health disparities for the populations most vulnerable in a changing climate. How PPH interventions collect and aggregate data, decide what to measure, and analyze data pose potential issues around privacy, neglecting social determinants of health, and introducing algorithmic bias into climate responses. Adopting a health justice framework, guided by broader social and climate justice tenets, can reveal principles and policy actions which may guide more responsible implementation of PPH in climate responses.